2019
DOI: 10.1002/anie.201814544
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Stable n‐Type Thermoelectric Materials Enabled by Organic Diradicaloids

Abstract: Air-stable n-type thermoelectric materials are recognized as an important and challenging topic in organic thermoelectrics (OTEs) because conventional n-type OTE materials prepared by chemical doping are highly volatile upon exposure to air.B esides,d oping efficiency and microstructure are hard to control with the incorporation of external dopants. We report herein the design and synthesis of unconventional ntype OTEmaterials based on the diradicaloids 2DQQT-S and 2DQQT-Se,w hicha re proved to be neutral sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 47 publications
2
96
0
Order By: Relevance
“…Diradicals and diradicaloids are of great current interest because of their unique structural and conceptional value, but also because of their potential applications in thermoelectric generators and spintronics . In the literature, diradicals having triplet ground states and singlet ground states with thermally accessible low‐lying triplet states are described.…”
Section: Figurementioning
confidence: 99%
“…Diradicals and diradicaloids are of great current interest because of their unique structural and conceptional value, but also because of their potential applications in thermoelectric generators and spintronics . In the literature, diradicals having triplet ground states and singlet ground states with thermally accessible low‐lying triplet states are described.…”
Section: Figurementioning
confidence: 99%
“…These organic TMs demonstrated advantages for assembling flexible TEG devices, but their low Seebeck coefficient and low electrical conductivity resulted in poor ZT values as well as lower power factors than those of inorganic TMs, which limits their applications. To improve their thermoelectric properties, efforts were made to increase these polymers' conductivity by doping, dedoping, and implementing a hybrid with high conductive carbon/metal materials . For instance, Kim et al reported that the dimethyl sulfoxide (DMSO) doped PEDOT:PSS derived a maximum polymer ZT value of 0.42 at room temperature .…”
Section: Materials For Energy Conversion Devicesmentioning
confidence: 99%
“…The covalently locked coplanar conformation of a conjugated ladder-type backbone, 1 in contrast with conventional non-ladder polymers with torsional rotation, allows for extensive intrachain delocalization of molecular orbitals and transport of quasi-particles such as charges, excitons, polarons, and spins. [2][3][4] The rigid coplanar conformation can also enhance interchain electronic coupling of conjugated ladder polymers due to the small reorganization energy of a rigid system upon electron transfer or photoexcitation, [5][6][7][8] which is important for solid-state materials properties. In addition, a signicantly higher activation energy is required to break the double-stranded backbones of a ladder polymer, translating to high stability that is important for applications under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%